Prevention of Nosocomial Infections in Critically Ill Patients With Lactoferrin: A Randomized, Double-Blind, Placebo-Controlled Study. Issue 9 (September 2018) - Muscedere, John; Maslove, David M.; Boyd, J. Gordon; O'Callaghan, Nicole; Sibley, Stephanie; Reynolds, Steven; Albert, Martin; Hall, Richard; Jiang, Xuran; Day, Andrew G.; Jones, Gwyneth; Lamontagne, Francois
Abstract : Objective: To obtain preliminary evidence for the efficacy of lactoferrin as a preventative measure for nosocomial infections and inform the conduct of a definitive study. Design: Phase 2, multicenter, randomized, double-blind, placebo-controlled study. Setting: Medical-surgical ICUs. Patients: Adult, critically ill patients receiving invasive mechanical ventilation. Interventions: Randomized, eligible, consenting patients expected to require invasive mechanical ventilation more than 48 hours received lactoferrin both enterally and via an oral swab or a placebo of sterile water for up to 28 days. Measurements and Main Results: Of the 214 patients who were randomized, 212 received at least one dose of the intervention and were analyzed (107 lactoferrin and 105 placebo). Protocol adherence was 87.5%. Patients receiving lactoferrin were older (mean [SD], 66.3 [13.5] vs 62.5 [16.2] yr), had a higher Acute Physiology and Chronic Health Evaluation II score (26.8 [7.8] vs 23.5 [7.9]), and need for vasopressors (79% vs 70%). Antibiotic-free days (17.3 [9.0] vs 18.5 [7.1]; p = 0.91) and nosocomial infections (0.3 [0.7] vs 0.4 [0.6] per patient; p = 0.48) did not differ between lactoferrin and placebo groups, respectively. Clinical outcomes for lactoferrin versus placebo were as follows: ICU length of stay (14.5 [18.0] vs 15.0 [37.3] d; p = 0.82), hospital length of stay (25.0 [25.9] vs 28.1 [44.6] d; p = 0.57), hospital mortality (41.1% vs 30.5%; p = 0.11), and 90-day mortality (44.9% vs 32.4%; p = 0.06). Biomarker levels did not differ between the groups. Conclusions: Lactoferrin did not improve the primary outcome of antibiotic-free days, nor any of the secondary outcomes. Our data do not support the conduct of a larger phase 3 trial. Abstract : Supplemental Digital Content is available in the text.